Emerging developments in China’s ship-induced oil pollution damage liability regime: a perspective from the revised draft of China’s maritime law - Ha, Runnan; Wei, Linyun; Li, Haoguang (Frontiers in Marine Science, 2025)
This article examines China’s evolving legal framework for ship-induced oil pollution damage liability system, focusing on the 2024 Draft Amendment to the Maritime Law. Historically, the development of this system in China has been achieved through accession to international conventions, domestic legislative transformation, and the improvement of supporting systems. However, fragmented rules and outdated liability limits hindered effective compensation. DAML introduces a dedicated chapter on oil pollution damage, establishing strict liability for shipowners, defining compensation scope, and mandating an “Insurance and Fund” dual safeguard system. It further clarifies joint liability for multi-ship spills and conflict-of-law rules favoring the lex loci damni. The study argues that this revision bridges gaps between international standards and domestic law while addressing judicial inconsistencies. In order to refine this system, this article conducts an analysis in conjunction with DAML revision text and puts forward optimization suggestions from four perspectives: improving the legal system, providing case law guidance, enhancing government supervision, and perfecting supporting legal safeguards.